(3GdeMGSHI GdMchejI (B/s - (3GSeGYjd, GSeGYjd Ndjds; (3YOS, fGFd MSf s ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2010)
(3GdGWGQ GdfXQj ddeMGSHI GdMchejI , GdfXGe GdeMGSHj GdMchej GdCQOfj , GdJWHjbGJ GdYdejI h GdeYGdLGJ GdbjOjI ddMSGHGJ GdMchejI (B: (3MSGHGJ GdehGRfI GdGjQGOGJ GdYGeI , MSGHGJ GdfabGJ hGdSda h GdGeGfGJ , GdMSGHGJ GdhSjWI GdCNQi , GdMSGHGJ GdNJGejI h GNjQG GdJMdjd GdeGdj GdMchej (B.s
(3eQGLY U(B.525s
Keywords: (3GdeMGSHIs; (3GdeMGSHI GdMchejIs; (3JObjb GdMSGHGJ GdMchejI(B- (3GdCQOfs